Producción de uvilla (Physalis peruviana l.) con dos abonos orgánicos humus y gallinaza y dos dosis en la finca Gabriela del cantón Pangua provincia de Cotopaxi 2014 - Basantes Esparza, Gabriela Piedad (2015)
In the present investigation the assessment of production uvilla (Physalis peruviana L.) with two organic humus and manure fertilizers and two doses in Gabriela land of Pangua Canton, Cotopaxi Province, for which the main objectives was established, establish the Uvilla’s production, to determine the effect of two different doses of organic fertilizers, and an economic analysis of production per treatment. Into the investigation we used a randomized block design (RCBD) was handled three repetitions and five treatments including the control. The data were collected according to plant growth every month for a period of 136 days, the changeful studied were: plant height whose best treatment was 60% of manure with a height of 142.07 cm....